Soluble and membrane-bound interleukin (IL)-15 Rα/IL-15 complexes mediate proliferation of high-avidity central memory CD8+ T cells for adoptive immunotherapy of cancer and infections. (31st August 2016) - Hasan, A N; Selvakumar, A; Shabrova, E; Liu, X-R; Afridi, F; Heller, G; Riviere, I; Sadelain, M; Dupont, B; O'Reilly, R J
Summary: The lack of persistence of infused T cells is a principal limitation of adoptive immunotherapy in man. Interleukin (IL)-15 can sustain memory T cell expansion when presented in complex with IL-15Rα (15Rα/15). We developed a novel in-vitro system for generation of stable 15Rα/15 complexes. Immunologically quantifiable amounts of IL-15 were obtained when both IL-15Rα and IL-15 genes were co-transduced in NIH 3T3 fibroblast-based artificial antigen-presenting cells expressing human leucocyte antigen (HLA) A:0201, β2 microglobulin, CD80, CD58 and CD54 [A2-artificial antigen presenting cell (AAPC)] and a murine pro-B cell line (Baf-3) (A2-AAPC 15Rα/15 and Baf-3 15Rα/15 ). Transduction of cells with IL-15 alone resulted in only transient expression of IL-15, with minimal amounts of immunologically detectable IL-15. In comparison, cells transduced with IL-15Rα alone (A2-AAPC Rα ) demonstrated stable expression of IL-15Rα; however, when loaded with soluble IL-15 (sIL-15), these cells sequestered 15Rα/15 intracellularly and also demonstrated minimal amounts of IL-15. Human T cells stimulated in vitro against a viral antigen (CMVpp65) in the presence of 15Rα/15 generated superior yields of high-avidity CMVpp65 epitope-specific T cells [cytomegalovirus-cytotoxic T lymphocytes (CMV-CTLs)] responding to ≤ 10 − 13 M peptide concentrations, and lysing targets cells at lower effector : target ratios (1 : 10 and 1 : 100), where sIL-15, sIL-2 or sIL-7 CMV-CTLs demonstrated minimal or no activity. Both soluble and surface presented 15Rα/15, but not sIL-15, sustained in-vitro expansion of CD62L + and CCR7 + central memory phenotype CMV-CTLs (TCM ). 15Rα/15 complexes represent a potent adjuvant for augmenting the efficacy of adoptive immunotherapy. Such cell-bound or soluble 15Rα/15 complexes could be developed for use in combination immunotherapy approaches. Graphical Abstract: